2019
DOI: 10.1080/13814788.2019.1681194
|View full text |Cite
|
Sign up to set email alerts
|

GPs who volunteer to be first responders for out-of-hospital cardiac arrest: A qualitative study

Abstract: GPs contribute significantly to survival from cardiac arrest. In Ireland, emergency medical services now alert volunteer GP first responders. GPs volunteer for this role because of their relationship to the community. GP first responders provide holistic cardiac arrest care including basic life support, team working with paramedics, critical decision-making and psychosocial care for bystanders and family members. ABSTRACTBackground: Out-of-hospital cardiac arrest (OHCA) is a major cause of premature mortality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This research has concerned initiatives such as Sms-lifesavers and community first responders (CFR) [ 3 8 ]. This research has typically been conducted on small samples of volunteers using qualitative approaches such as interviews or focus groups [ 9 12 ]. As a result, many themes have been proposed as important for how volunteers experience their role and their motivation for continuing.…”
Section: Introductionmentioning
confidence: 99%
“…This research has concerned initiatives such as Sms-lifesavers and community first responders (CFR) [ 3 8 ]. This research has typically been conducted on small samples of volunteers using qualitative approaches such as interviews or focus groups [ 9 12 ]. As a result, many themes have been proposed as important for how volunteers experience their role and their motivation for continuing.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that some volunteers Sørensen et al J Trauma Resusc Emerg Med (2023) 31:79 participate as first responders for the thrill and to obtain an "adrenaline rush". This group includes not only laypersons but also general practitioners who wish to receive an "adrenaline rush" [36] as a VFR. Voluntary laypersons describe other voluntary laypersons as "blue-light junkies" [2].…”
Section: Ethical Challenges Concerning Collaboration With Volunteer F...mentioning
confidence: 99%
“…At the outset we targeted a total sample of between 16-20 participants with approximate thirds representing Paramedics, GPs, and Practice Nurses/Managers (as a combined group). We based this sample size target on our previous experience of conducting qualitative research and the overall aim of achieving a thorough understanding of the phenomenon under study [28][29][30] .…”
Section: Recruitmentmentioning
confidence: 99%